The provincial Landtag in Silesia (1824–1848) compared with other similar institutions in Prussia - Kruszewski, Tomasz (The Opole Studies in Administration and Law, 2016)
The author presents the evolution of the authority established in Prussia in 1824, within the polity boundaries of the country, following the defeat suffered by Prussia in the war with Napoleon. The presentation of Landtag which was functioning in Silesia is the starting point to make a comparison between this institution and others which were established on the parallel basis in other Prussian provinces. Differences and similarities between them are shown.